Critical Factors Influencing the Occurrence of Vibrio Cholerae in the Environment of Bangladesh - Huq, Anwar; Sack, R. Bradley; Nizam, Azhar; Longini, Ira M.; Nair, G. Balakrish; Ali, Afsar; Morris, J. Glenn; Khan, M. N. Huda; Siddique, A. Kasem; Yunus, Mohammed; Albert, M. John; Sack, David A.; et al. (Applied and Environmental MicrobiologyAppl. Environ. Microbiol.Applied and Environmental MicrobiologyAppl. Environ. Microbiol., 2005)
The occurrence of outbreaks of cholera in Africa in 1970 and in Latin America in 1991, mainly in coastal communities, and the appearance of the new serotype Vibrio cholerae O139 in India and subsequently in Bangladesh have stimulated efforts to understand environmental factors influencing the growth and geographic distribution of epidemic Vibrio cholerae serotypes. Because of the severity of recent epidemics, cholera is now being considered by some infectious disease investigators as a “reemerging” disease, prompting new work on the ecology of vibrios. Epidemiological and ecological surveillance for cholera has been under way in four rural, geographically separated locations in Bangladesh for the past 4 years, during which both clinical and environmental samples were collected at biweekly intervals. The clinical epidemiology portion of the research has been published (Sack et al., J. Infect. Dis. 187:96-101, 2003). The results of environmental sampling and analysis of the environmental and clinical data have revealed significant correlations of water temperature, water depth, rainfall, conductivity, and copepod counts with the occurrence of cholera toxin-producing bacteria (presumably V. cholerae). The lag periods between increases or decreases in units of factors, such as temperature and salinity, and occurrence of cholera correlate with biological parameters, e.g., plankton population blooms. The new information on the ecology of V. cholerae is proving useful in developing environmental models for the prediction of cholera epidemics.